Implementasi Metode ARAS Pada Sistem Pendukung Keputusan Rekomendasi Penerimaan Karyawan - Thesa Noveninta Ginting; Muhammad Syahrizal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Recommendations for employee recruitment are a fact that in an organization is always open. With recommendations for employee recruitment, new jobs and other activities are created. PT. Pegadaian (Persero) is a State-Owned Enterprise (BUMN) in the financial sector which operates in three corporate businesses, including financing, gold and various services. PT. Pegadaian annually recruits new employees, which in the employee recruitment process here at PT. Pegadaian also recruits employees with disabilities. Disabled employees are employees who have mental, physical limitations and have extensive intellectual and sensory knowledge for a long period of time so that interacting with the environment and society can encounter obstacles that make it difficult for them to participate fully based on equal rights. The solution to the problem above is to build a decision support system for hiring disabled employees at PT. Pawnshop. The method chosen to support solving the problem above is the Additive Ratio Assessment (ARAS) method, namely by giving weight to each available alternative option. This research produces a decision support system that can recommend the acceptance of employees with disabilities at PT. Pegadaian uses the Additive Ratio Assessment (ARAS) method. A trial was carried out by entering a data sample of 15 (fifteen) employees with disabilities. With the decision support system, it can provide recommendations for accepting disabled employees at PT Pegadaian based on ranking, from 15 candidates for hiring disabled employees based on the largest ranking: Alternative 1 with a value of 0.9645, Alternative 2 with a value of 0.9139, and Alternative 3 with a value of 0. 9101